Accelerated degradation testing impacts the degradation processes in 3D printed amorphous PLLA - Malone, Luke P.; Best, Serena M.; Cameron, Ruth E. (Frontiers in Bioengineering and Biotechnology, 2024)
Additive manufacturing and electrospinning are widely used to create degradable biomedical components.This work presents important new data showing that the temperature used in accelerated tests has a significant impact on the degradation process in amorphous 3D printed poly-l-lactic acid (PLLA) fibres. Samples (c. 100 µm diameter) were degraded in a fluid environment at 37 0 C, 50 0 C and 80 0 C over a period of six months. Our findings suggest that across all three fluid temperatures, the fibres underwent bulk homogeneous degradation. A three-stage degradation process was identified by measuring changes in fluid pH, PLLA fibre mass, molecular weight and polydispersity index. At 37 0 C, the fibres remained amorphous but, at elevated temperatures, the PLLA crystallised. A short-term hydration study revealed a reduction in glass transition (Tg), allowing the fibres to crystallise, even at temperatures below the dry Tg. The findings suggest that degradation testing of amorphous PLLA fibres at elevated temperatures changes the degradation pathway which, in turn, affects the sample crystallinity and microstructure. The implication is that, although higher temperatures might be suitable for testing bulk material, predictive testing of the degradation of amorphous PLLA fibres (such as those produced via 3D printing or electrospinning) should be conducted at 37 0 C.